Assessing Human Resource Management Strategies and Their Influence on Job Satisfaction in Private Banks - Wadud, Hassan (Journal of Policy Options, 2022)
The rapid advancements in information and communication technology, shifts in workforce dynamics and personal values, the rise of the knowledge economy, and intensifying global competition have presented significant challenges for organizations across all sectors. These developments demand that companies not only adapt quickly but also find innovative ways to stay competitive and efficient. Among the various factors critical to overcoming these challenges, human resources have emerged as one of the most vital components. In today’s hyper-competitive business environment, organizations increasingly recognize that their success largely depends on effectively managing and developing their workforce. This recognition has led to a growing emphasis on Human Resource Management (HRM) practices, which play a key role in improving organizational performance by fostering employee satisfaction, engagement, and retention. HRM practices, ranging from recruitment and selection to training and development, performance appraisal, compensation management, and employee relations, are critical in aligning employee goals with organizational objectives. When employees are satisfied and motivated, it enhances productivity, reduces turnover, and ultimately contributes to the organization’s success. In the context of Bangladesh's private banking sector, where competition is fierce, and customer expectations are continuously evolving, HRM practices have become even more crucial. The sector faces unique challenges, including managing a diverse workforce, adhering to strict regulatory requirements, and navigating the impacts of globalization. In such an environment, effective HRM practices not only help in managing employee satisfaction but also play a strategic role in maintaining a competitive edge. The purpose of this study is to gain an in-depth understanding of the prevailing HRM practices in the private banking sector of Bangladesh and to assess their impact on employee satisfaction. By examining key HRM functions such as employee engagement, training and development, performance management, and compensation, the study aims to uncover how these practices influence employees' attitudes, motivation, and overall job satisfaction. Ultimately, the findings of this research can provide valuable insights for banking institutions looking to refine their HRM strategies to foster a more motivated, satisfied, and high-performing workforce. To conduct this research, a sample of 100 bank employees was selected from the chosen private banks. Out of the 100 distributed questionnaires, 88 were returned with valid responses, resulting in an 88% response rate. The questionnaire included a range of questions designed to assess nine key HRM dimensions: recruitment and selection systems, compensation packages, job security, career growth, training and development, management style, job design and responsibilities, reward and motivation, and the working environment. A five-point Likert scale was utilized to gauge employee perceptions and satisfaction across these dimensions. In the analysis, various statistical techniques, including the Z-test, mean, and proportion analysis, were employed to evaluate employee satisfaction levels. The findings of the study reveal that not all HRM dimensions in the private banking sector of Bangladesh equally contribute to employee satisfaction. Specifically, the research highlights significant dissatisfaction among employees regarding the compensation package, which ranked as the most critical concern. This is followed by dissatisfaction with reward and motivation, career growth opportunities, training and development programs, management style, and job design and responsibilities. Based on these findings, it is clear that improvements in these HRM dimensions are necessary to enhance employee satisfaction. Addressing these issues could play a crucial role in not only boosting employee morale but also improving overall organizational performance and long-term success within the competitive banking industry. Consequently, banks should consider revising their HRM strategies to focus on better compensation structures, clearer career advancement opportunities, more effective training, and development programs, and creating a more motivating work environment.